Analisis Sistem Pengendalian Internal Pemerintah dalam Meningkatkan Kualitas Laporan Keuangan Pemerintah Kota Palembang - Kiagus M Dimas Cattur Raihan; Muhammad Fahmi; Gumulya Sonny Marcel Kusuma (CV. Doki Course and Training, 2025)
Abstract : The research problem formulation is how the implementation of the government’s internal control system improves the quality of financial reports of the city of Palembang (case study at the Regional Revenue Agency of the City of Palembang). The aim is to analyze the implementation of the government's internal control system to enhance the quality of financial reports of the city of Palembang. This research is associative, aimed at identifying the relationship between two or more variables and their effects. The independent variable is the internal control system, and the dependent variable is the quality of financial reports. The population of the study consists of employees of the Regional Revenue Agency of the City of Palembang. The number of respondents was 4 heads of departments from the regional revenue agency of Palembang city, which consisted of the BPHTB & PBB department, other local tax departments, the collection department, planning and development of local revenue, as well as the control and local tax database department. Primary data is needed as the basis for analysis, while the data collection technique used is a questionnaire. The analysis method used is qualitative analysis. The results of the study indicate that the Internal Control System at the Regional Revenue Agency of Palembang City is functioning well and is capable of improving the quality of its financial reports.